Biophilic Design and Climate Change: Performance Parameters for Health - Africa, Julia; Heerwagen, Judith; Loftness, Vivian; Ryan Balagtas, Catherine (Frontiers in Built Environment, 2019)
Biophilic design is one of a number of trending design practices that rely on nature-based systems, engineering principles and design cues to improve environmental quality, health and efficiency. Biophilic design integrates but does not appropriate the contributions of other nature-based design techniques precisely because it can act as a platform or ‘interstitial tissue’, providing a connective language/practice/ethos that can unite disparate practices in the built environment more broadly. This paper provides an illustrative compilation of how biophilic design practices can directly support resilience in human health and the built environment on behalf of the International Living Future Institute’s Biophilic Design Advisory Board. We strongly advocate the use of metrics related to climate change mitigation as a dimension of performance analysis for biophilic design practices as a demonstration of professional mindfulness and responsibility.